2009
DOI: 10.1089/cbr.2008.0533
|View full text |Cite
|
Sign up to set email alerts
|

The Antitumor Effects of CIK Cells Combined with Docetaxel Against Drug-Resistant Lung Adenocarcinoma Cell Line SPC-A1/DTXin Vitroandin Vivo

Abstract: CIK cells plused with docetaxel demonstrated a prominent augmentation of antitumor activity against multidrug resistance lung adenocarcinoma cell lines both in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Immunotherapy stimulating the immune system and enhancing the patient's own anti-tumor ability is an alternative and promising way to treat cancer and overcome chemotherapy drug resistance [9,10]. In the 1980s, the lymphocytes activated by IL-2, were used for treating malignancies at advanced stage [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunotherapy stimulating the immune system and enhancing the patient's own anti-tumor ability is an alternative and promising way to treat cancer and overcome chemotherapy drug resistance [9,10]. In the 1980s, the lymphocytes activated by IL-2, were used for treating malignancies at advanced stage [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, CIK cells transfusion has evolved to become a promising way for overcoming chemotherapy resistance [9,10]. Liu et al reported that CIK cells possessed a higher antitumor cytotoxic activity against a drug-resistant lung adenocarcinoma cell line in vitro and they found CIK cells plused with docetaxel demonstrated a prominent augmentation of antitumor activity against multidrug resistance lung adenocarcinoma cell lines both in vitro and in vivo [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small remnant lesions in situ and metastatic cancer cells are the main reasons for recurrence. Immunotherapy, using various methods to restore and enhance the immune abilities of patients to eliminate cancer cells, is an alternative and promising option in treating cancers (Liu et al, 2009). Immunotherapy overcomes immunosuppression induced by cancer, surgery, or chemotherapeutic agents (Shi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Synergistic use of CIK cells and docetaxel demonstrated a stronger anti-tumor effect in several multidrug-resistant lung adenocarcinoma cell lines (Liu et al, 2009). The property of antagonistic drug resistance of DC-CIK cells makes it appropriate for improving the clinical outcome of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%